Preparation of modified graphene and graphene quantum dots and application of modified graphene and graphene quantum dots in fibers and films

By introducing Ce and Cl co-doping and phosphating treatment in the graphene preparation process, modified graphene quantum dots with high mechanical properties and antibacterial effects were prepared, and applied to fibers and thin films, the problems of complex and cost in the existing graphene preparation process are solved, and high-quality and low-cost graphene preparation and versatile applications are achieved.

CN119708892APending Publication Date: 2025-03-28HAINAN SIRUI NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411994755.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing graphene preparation process has problems such as high environmental requirements and complex preparation process, which is difficult to meet the needs of high quality and low cost.

Method used

The graphene co-doped with Ce and Cl was prepared by reacting compounds such as sodium citrate, urea, cyanochloride and cerium nitrate in an autoclave. Graphene quantum dots were prepared by ultrasonic and microwave phosphating treatment, and modified graphene films and nanofibers were formed by combining polymers.

Benefits of technology

It improves the mechanical properties and antibacterial effect of graphene, enhances the dispersion and biocompatibility of graphene quantum dots, and achieves the flexibility and versatility of fibers and films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708892A_ABST
    Figure CN119708892A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of graphene products, and particularly relates to preparation of modified graphene and graphene quantum dots and application of the modified graphene and the graphene quantum dots to fibers and films. As a novel carbon-based nano material, the graphene quantum dots have unique flexibility and ductility. The metal nanoparticles are utilized to modify the graphene, so that the mechanical property of the graphene is enhanced. And when the fiber and the film are applied to the fiber and the film, the flexibility of the fiber and the film is greatly improved, and meanwhile, the fiber and the film also have the biological functions of bacteria resistance, bacteriostasis, mildew prevention, mite removal, virus resistance, far infrared and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of graphene products, and specifically relates to a preparation process of modified graphene and graphene quantum dots, and in particular to the preparation of modified graphene and graphene quantum dots, and their application in fibers and films. Background Art

[0002] As a new type of two-dimensional carbon material, the theoretical research on graphene can be traced back to the middle of the last century. At first, Canadian physicists conducted theoretical research on graphene and found that it has unusual semi-metallic properties. Soon after, Boehm and others prepared a small amount of thin layer graphene by chemically reducing graphene oxide. It was not until 2004 that AKGeim, KS Novoselov and others successfully peeled graphene from graphite and won the Nobel Prize in Physics for their groundbreaking graphene two-dimensional material experiments. Since then, the world has ushered in a research boom on graphene. Graphene is a carbon atom thick, and carbon atoms are sp 2 Hybrid orbitals form a planar thin film two-dimensional material with a honeycomb hexagonal lattice. Due to its unique physical structure, graphene has many excellent physical properties. Graphene has excellent physical properties. Since its advent, researchers have been constantly exploring high-quality and low-cost graphene preparation methods. Nowadays, according to the different preparation forms, it can be roughly divided into two types, namely the bottom-up method and the top-down method. For the bottom-up method, non-graphite carbon sources are generally used in the preparation, mainly using chemical methods such as cracking. The preparation process has high environmental requirements and generally requires high temperature and inert gas protection. This method is suitable for the preparation of graphene films and foam graphene materials with three-dimensional structures. The top-down method generally uses graphite as the main raw material and is prepared by exfoliation. Graphene is a planar thin film material with a honeycomb lattice composed of carbon atoms. Based on its special structure, graphene has many excellent physical properties, which makes it have the potential to be used in new components.

[0003] Graphene quantum dots (GQDs) refer to an emerging carbon material with a graphene sheet size of less than 100 nm and a sheet number of less than 10 layers. Since the discovery of graphene, its unique optical properties, excellent chemical stability and good biocompatibility have attracted great attention from researchers in various fields. The development of graphene quantum dots has further promoted the entry of graphene-based materials into the biomedical field. Therefore, the present invention designs a preparation process for modified graphene and graphene quantum dots. Applying it in fibers and films greatly improves the flexibility of fibers and films. In addition, the material also has biological functions such as antibacterial, mildew and mite prevention, antiviral, and far infrared. Therefore, the present invention is of great significance for promoting social development. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a preparation process of modified graphene and graphene quantum dots, and apply them in fibers and films. The present invention is achieved through the following technical solutions: S1. Weigh 2-3 g sodium citrate, 5-10 g urea, 1-2 g cyanuric chloride and 3-5 g cerium nitrate, then dissolve them in a beaker containing 30-50 mL N,N-dimethylformamide (DMF), place on a magnetic stirrer, stir for 15-20 min, transfer to a 100 mL high-pressure reactor, and react at a constant temperature of 150-190 °C for 8-10 h. After the reaction is completed, cool to room temperature. Take out the brown-black solution after the reaction, then mix the solution after the reaction with ethanol in a volume ratio of 1:2, ultrasonicate for 3-5 min, and heat at 8000 r min. -1 The product was centrifuged in a high-speed refrigerated centrifuge for 8-11 min, and the obtained product was dissolved in ethanol again, ultrasonicated for 2-5 min, and centrifuged for 10-15 min. After repeated washing twice, the obtained black solid product was dissolved in water, ultrasonicated for 5-7 min to quickly disperse it, and loaded into a dialysis bag with a molecular weight cutoff of 1000D-2000D, and dialyzed in a 1L beaker. Ultrapure water was replaced every 4 hours on the first day, and then every 8 hours. After dialysis for 48 hours, the solution was poured into a 50mL round-bottom flask and concentrated to 10-30 mL using a rotary evaporator. The rotary evaporation temperature was controlled at 50-55°C, and then loaded into a 50mL centrifuge tube. The material was freeze-dried using a freeze dryer to obtain a black solid, which is Ce and Cl co-doped graphene. In this step, Cl has a stronger electronegativity and Ce has a larger valence state. The co-doping of the two can greatly improve the mechanical properties and antibacterial effects of graphene. In addition, the introduction of Ce and Cl is conducive to dispersing graphene sheets through electrostatic repulsion and better controlling the number of material layers.

[0005] S2. Take 35-50 mL of 0.15-0.3M sodium hypophosphite solution and place it in a 100 mL microwave reactor. Add 5-9 g of Ce and Cl co-doped graphene prepared in step S1, stir evenly, and ultrasonicate for 40 min. Place the reactor in a microwave reactor. Set the temperature to 130-150°C, the microwave power to 300-600W, and the microwave time to 20-30 min. After cooling to room temperature, heat the liquid at 9000 r min. -1Centrifuge for 10 min in a high-speed centrifuge, and after drying, graphene quantum dots co-doped with Ce and Cl containing P can be obtained. Ultrasonic treatment in this step is beneficial to nano-graphene. Phosphating under the action of microwaves is beneficial to the segmentation of graphene to prepare graphene quantum dots, avoiding the reagglomeration of quantum dots, and there is a synergistic effect between P, Ce and Cl, ensuring good dispersion of graphene quantum, showing good antibacterial properties while ensuring excellent biocompatibility. The graphene quantum dots prepared in this step are about 5 nm. In addition, this step prepares human graphene quantum dots grafted with mite removal functional bonds, which can effectively remove mites.

[0006] S3, weigh 9-18 g of the modified graphene quantum dots prepared in step S2, 13-27 g of the high molecular weight polymer polysulfone and 0.5-0.8 g of polyimide, dissolve them in a beaker containing 5-8 mL of polyethylene glycol and 60-75 mL of dimethylacetamide, and then put them in a magnetic stirrer and stir for 30-45 min to obtain a casting solution; the stirred casting solution is allowed to stand for degassing for 36-48 h until the solution is uniform and free of bubbles. When scraping the film, first place the casting solution on a polyester non-woven fabric that has been uniformly soaked with dimethylacetamide on a glass plate, and then use an automatic scraping machine to evenly apply a coating with a thickness of 0.2-0.5 mm. After evaporating in the air for 15-30 s, immediately place the polyester non-woven fabric coated with the casting solution in deionized water at 25°C for phase inversion, then take out the film and wash it repeatedly with deionized water, and store it in deionized water for standby use. When scraping the film, the relative humidity of the environment is controlled at 40%-50% and the ambient temperature is controlled at 25°C to obtain a film containing modified graphene quantum dots. The film has excellent mechanical properties, thermal stability and conductivity, and can be used in flexible electronics, sensors, energy storage devices, etc.

[0007] S4. Weigh 8-11 g of the modified graphene quantum dots prepared in step S2, dissolve in 30-40 mL of N,N-dimethylformamide and 20-32 mL of anhydrous ethanol, then add 3-5 mL of 30% H2O2, stir for 8-10 min, then add 5-8 g of polyvinyl pyrrolidone and 10-15 mL of 2-methoxyethanol, stir for 12-20 h. The reaction is quite violent, so safety precautions should be taken. Then put the mixed solution into a syringe for the next step. Apply a voltage of 13-18 kV between the syringe and the aluminum foil at a distance of 15-20 cm. -1 The mixed solution is sprayed at a rate of , and nanofibers containing modified graphene are formed by electrostatic spinning. The graphene nanofibers prepared by electrostatic spinning in this step have a content of 0.1-0.5%.

[0008] Preferably: in step S1, 2 g of sodium citrate, 5 g of urea, 1 g of cyanuric chloride and 3 g of cerium nitrate are weighed, and then dissolved in a beaker containing 30 mL of N,N-dimethylformamide, and then placed on a magnetic stirrer, stirred for 15 min, transferred to a 100 mL high-pressure reactor, and reacted at a constant temperature of 150 ° C for 8 h; after the reaction is completed, cooled to room temperature; the brown-black solution after the reaction is taken out, and then the solution after the reaction is mixed with ethanol in a volume ratio of 1:2, and then ultrasonicated for 3 min at 8000 r min -1 The product was centrifuged in a high-speed refrigerated centrifuge for 8 min, and the obtained product was dissolved in ethanol again, ultrasonicated for 2 min, and centrifuged for 10 min. After repeated washing twice, the obtained black solid product was dissolved in water, ultrasonicated for 5 min to make it quickly dispersed, and loaded into a dialysis bag with a molecular weight cutoff of 1000D, and dialyzed in a 1L beaker. Ultrapure water was replaced every 4 hours on the first day, and then every 8 hours. After dialysis for 48 hours, the solution was poured into a 50 mL round-bottom flask and concentrated to 10 mL using a rotary evaporator. The rotary evaporation temperature was controlled at 50 ℃, and then loaded into a 50 mL centrifuge tube. The material was freeze-dried using a freeze dryer to obtain a black solid, which is Ce and Cl co-doped graphene.

[0009] Preferably: in step S1, 3 g of sodium citrate, 10 g of urea, 2 g of cyanuric chloride and 5 g of cerium nitrate are weighed, and then dissolved in a beaker containing 50 mL of N,N-dimethylformamide, and then placed on a magnetic stirrer, stirred for 20 min, transferred to a 100 mL high-pressure reactor, and reacted at a constant temperature of 190 ° C for 8-10 h; after the reaction is completed, it is cooled to room temperature; the brown-black solution after the reaction is taken out, and then the solution after the reaction is mixed with ethanol in a volume ratio of 1:2, and then ultrasonicated for 5 min at 8000 r min -1 The product was centrifuged in a high-speed refrigerated centrifuge for 11 min, and the obtained product was dissolved in ethanol again, ultrasonicated for 5 min, and centrifuged for 15 min. After repeated washing twice, the obtained black solid product was dissolved in water, ultrasonicated for 7 min to make it quickly dispersed, and loaded into a dialysis bag with a molecular weight cutoff of 1000D-2000D, and dialyzed in a 1L beaker. Ultrapure water was replaced every 4 hours on the first day, and then every 8 hours. After dialysis for 48 hours, the solution was poured into a 50 mL round-bottom flask and concentrated to 30 mL using a rotary evaporator. The rotary evaporation temperature was controlled at 55°C, and then loaded into a 50 mL centrifuge tube. The material was freeze-dried using a freeze dryer to obtain a black solid, which is Ce and Cl co-doped graphene.

[0010] Preferably: 35 mL of 0.15 M sodium hypophosphite solution in S2 is weighed and placed in a 100 mL microwave reactor, 5 g of Ce and Cl co-doped graphene prepared in step S1 is added, stirred evenly, and ultrasonically treated for 40 min; the reactor is placed in a microwave reactor; the temperature is set to 130 ° C, the microwave power is 300 W, and the microwave time is 20 min; after cooling to room temperature, the liquid is heated at 9000 r min -1 After centrifugation in a high-speed centrifuge for 10 min and drying, P-containing Ce and Cl co-doped graphene quantum dots can be obtained.

[0011] Preferably: 50 mL of 0.3M sodium hypophosphite solution in S2 is weighed and placed in a 100 mL microwave reactor, 9 g of Ce and Cl co-doped graphene prepared in step S1 is added, stirred evenly, and ultrasonically treated for 40 min; the reactor is placed in a microwave reactor; the temperature is set to 150°C, the microwave power is 600 W, and the microwave time is 30 min; after cooling to room temperature, the liquid is heated at 9000 r min -1 The resultant was centrifuged in a high-speed centrifuge for 10 min and dried to obtain P-containing Ce and Cl co-doped graphene quantum dots.

[0012] Preferably: in the step S3, 9 g of the modified graphene quantum dots prepared in step S2, 13 g of the high molecular weight polymer polysulfone and 0.5 g of polyimide are weighed and dissolved in a beaker containing 5 mL of polyethylene glycol and 60 mL of dimethylacetamide, and then placed in a magnetic stirrer and stirred for 30 min to obtain a casting solution; the stirred casting solution is allowed to stand for degassing for 36 h until the solution is uniform and free of bubbles; when scraping the film, the casting solution is first placed on a polyester non-woven fabric that has been uniformly soaked with dimethylacetamide and attached to a glass plate, and then an automatic scraping machine is used to uniformly apply a coating with a thickness of 0.2 mm. After evaporating in the air for 15 s, the polyester non-woven fabric coated with the casting solution is immediately placed in deionized water at 25°C for a phase inversion process, and then the film is taken out and repeatedly washed with deionized water, and stored in deionized water for standby use; when scraping the film, the relative humidity of the environment is controlled at 40% and the ambient temperature is controlled at 25°C, and a thin film containing modified graphene quantum dots can be obtained.

[0013] Preferably: in S3, 18 g of the modified graphene quantum dots prepared in step S2, 27 g of the high molecular weight polymer polysulfone and 0.8 g of polyimide are weighed and dissolved in a beaker containing 8 mL of polyethylene glycol and 75 mL of dimethylacetamide, and then placed in a magnetic stirrer and stirred for 45 min to obtain a casting solution; the stirred casting solution is allowed to stand for degassing for 48 h until the solution is uniform and free of bubbles; when scraping the film, the casting solution is first placed on a polyester non-woven fabric that has been uniformly soaked with dimethylacetamide and attached to a glass plate, and then an automatic scraping machine is used to uniformly apply a coating with a thickness of 0.5 mm. After evaporating in the air for 30 s, the polyester non-woven fabric coated with the casting solution is immediately placed in deionized water at 25°C for a phase inversion process, and then the film is taken out and repeatedly washed with deionized water, and stored in deionized water for standby use; when scraping the film, the relative humidity of the environment is controlled at 50% and the ambient temperature is controlled at 25°C, and a thin film containing modified graphene quantum dots can be obtained.

[0014] Preferably: in said S4, 8 g of the modified graphene quantum dots prepared in step S2 are weighed and dissolved in 30 mL of N,N-dimethylformamide and 20 mL of anhydrous ethanol, and then 3 mL of 30% H2O2 is added, stirred for 8 min, and then 5 g of polyvinyl pyrrolidone and 10 mL of 2-methoxyethanol are added, and stirred for 12 h; then the mixed solution is placed in a syringe for the next step; a voltage of 13 kV is applied between the syringe and the aluminum foil at a distance of 15 cm; and 0.4 mLh -1 The mixed solution is ejected at a rate of , and nanofibers containing modified graphene are formed by electrospinning.

[0015] Preferably: in said S4, 11 g of the modified graphene quantum dots prepared in step S2 are weighed and dissolved in 40 mL of N,N-dimethylformamide and 32 mL of anhydrous ethanol, and then 5 mL of 30% H2O2 is added, stirred for 10 min, and then 8 g of polyvinyl pyrrolidone and 15 mL of 2-methoxyethanol are added, stirred for 20 h, and then the mixed solution is put into a syringe for the next step; a voltage of 18 kV is applied between the syringe and the aluminum foil at a distance of 20 cm; and the mixture is stirred at 0.6 mL / min. -1 The mixed solution is ejected at a rate of , and nanofibers containing modified graphene are formed by electrospinning.

[0016] The invention is beneficial in that: 1. The synthesis process of the present invention has the advantages of simple operation, fast reaction speed, green environmental protection, and high yield.

[0017] 2. In the modified graphene quantum dots prepared by the present invention, Cl has a stronger electronegativity and Ce has a larger valence state. The co-doping of the two can greatly improve the mechanical properties and antibacterial effects of graphene.

[0018] 3. The introduction of Ce and Cl into the modified graphene quantum dots prepared by the present invention is conducive to dispersing the graphene sheets through electrostatic repulsion and better controlling the number of layers of the material.

[0019] 4. Ultrasonic treatment in the modified graphene quantum dots prepared by the present invention is beneficial to nano-synthesizing graphene.

[0020] 5. The present invention phosphates graphene under the action of microwaves, which is beneficial to the segmentation of graphene to prepare graphene quantum dots, avoiding the reagglomeration of quantum dots. In addition, there is a synergistic effect between P, Ce and Cl, which ensures that the graphene quantum is well dispersed, exhibits good antibacterial properties and ensures excellent biocompatibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a scanning electron microscope image of the modified graphene prepared in Example 1 of the present invention.

[0022] Figure 2 This is a transmission electron microscopy image of the modified graphene quantum dots prepared in Example 2 of the present invention.

[0023] Figure 3 This is an AFM scan of the modified graphene prepared in Example 2 of the present invention.

[0024] Figure 4 This is an AFM scan of the graphene prepared in Comparative Example 6 of the present invention.

[0025] Figure 5 This is a transmission electron microscope high-resolution image of the modified graphene quantum dots prepared in Example 3 of the present invention.

[0026] Figure 6 This is a transmission electron microscope high-resolution image of the modified graphene quantum dots prepared in Comparative Example 7 of the present invention.

[0027] Figure 7 This is a transmission electron microscope image of the nanofibers prepared in Example 4 of the present invention.

[0028] Figure 8 This is a transmission electron microscope image of the nanofibers prepared in Comparative Example 8 of the present invention. DETAILED DESCRIPTION

[0029] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.

[0030] Example 1

[0031] S1. Weigh 2 g sodium citrate, 5 g urea, 1 g cyanuric chloride and 3 g cerium nitrate, then dissolve them in a beaker containing 30 mL N,N-dimethylformamide (DMF), place on a magnetic stirrer, stir for 15 min, transfer to a 100 mL autoclave, and react at 150 °C for 8 h. After the reaction is completed, cool to room temperature. Take out the brown-black solution after the reaction, then mix the solution after the reaction with ethanol in a volume ratio of 1:2, ultrasonicate for 3 min, and heat at 8000 r min. -1 The product was centrifuged on a high-speed refrigerated centrifuge for 8 min, and the obtained product was dissolved in ethanol again, ultrasonicated for 2 min, and centrifuged for 10 min. After repeated washing twice, the obtained black solid product was dissolved in water, ultrasonicated for 5 min to make it quickly dispersed, and placed in a dialysis bag with a molecular weight cutoff of 1000D, and dialyzed in a 1L beaker. Ultrapure water was replaced every 4 h on the first day, and then every 8 h. After dialysis for 48 h, the solution was poured into a 50 mL round-bottom flask and concentrated to 10 mL using a rotary evaporator. The rotary evaporation temperature was controlled at 50 ° C, and then loaded into a 50 mL centrifuge tube. The freeze-dried material was freeze-dried using a freeze dryer to obtain a black solid, which was graphene co-doped with Ce and Cl. In this step, Cl has a strong electronegativity and Ce has a large valence state. The co-doping of the two can greatly improve the mechanical properties and antibacterial effects of graphene, and the introduction of Ce and Cl is conducive to dispersing graphene sheets through electrostatic repulsion and better controlling the number of layers of the material.

[0032] S2, take 50 mL of 0.3M sodium hypophosphite solution and place it in a 100 mL microwave reactor, add 9 g of Ce and Cl co-doped graphene prepared in step S1, stir evenly, and ultrasonicate for 40 min. Place the reactor in a microwave reactor. Set the temperature to 150°C, microwave power to 600W, and microwave time to 30 min. After cooling to room temperature, heat the liquid at 9000 r min. -1The mixture was centrifuged in a high-speed centrifuge for 10 min and dried to obtain graphene quantum dots co-doped with Ce and Cl containing P. Ultrasonic treatment in this step is beneficial to nano-fiberization of graphene. Phosphating under microwave action is beneficial to the segmentation of graphene to prepare graphene quantum dots, avoiding the reaggregation of quantum dots. In addition, there is a synergistic effect between P, Ce and Cl, which ensures that graphene quantum is well dispersed, exhibits good antibacterial properties and ensures excellent biocompatibility.

[0033] S3, weigh 9 g of the modified graphene quantum dots prepared in step S2, 13 g of high molecular weight polymer polysulfone and 0.5 g of polyimide, dissolve them in a beaker containing 5 mL of polyethylene glycol and 60 mL of dimethylacetamide, and then put them in a magnetic stirrer and stir for 30 min to obtain a casting solution; the stirred casting solution is allowed to stand for degassing for 36 h until the solution is uniform and free of bubbles. When scraping the film, first place the casting solution on a polyester non-woven fabric that has been uniformly soaked with dimethylacetamide on a glass plate, and then use an automatic scraping machine to evenly apply a coating with a thickness of 0.2 mm. After evaporating in the air for 15 s, immediately put the polyester non-woven fabric coated with the casting solution into deionized water at 25°C for phase inversion, then take out the film and wash it repeatedly with deionized water, and store it in deionized water for standby use. When scraping the film, the relative humidity of the environment is controlled at 40%, and the ambient temperature is controlled at 25°C, and a film containing modified graphene quantum dots can be obtained.

[0034] Comparative Example 1: In step S1, except that 3 g of cerium nitrate is not added, the remaining steps are the same as those of Example 1.

[0035] Comparative Example 2: In step S1, except that 1 g of cyanuric chloride is replaced with 1 g of cyanuric chloride, the remaining steps are the same as those in Example 1.

[0036] Comparative Example 3: In step S1, except that 3 g of cerium nitrate and 1 g of cyanuric chloride are not added, the remaining steps are the same as those of Example 1.

[0037] Figure 1 This is a scanning electron microscope image of the modified graphene prepared in Example 1 of the present invention. Figure 1It can be seen that the modified graphene prepared by the present invention is a two-dimensional sheet structure, and the doping of Ce and Cl changes its surface properties and functionalization degree, which breaks through some limitations of unmodified graphene in many practical applications. The shortcomings of poor dispersibility and chemical inertness of the original graphene in the solvent are improved, and its large-scale application in the fields of composite materials, catalysts, sensors, biomedicine, etc. is improved. The antibacterial rate of the graphene quantum dot film prepared by Example 1 of the present invention and Comparative Examples 1-3 is tested. The present invention is tested in accordance with GB / T 20944.3-2008 "Evaluation of Antibacterial Properties of Textiles". The mite avoidance rate of the present invention is tested in accordance with GB / T 24253-2009 "Evaluation of Chronic Performance of Textiles 9.1 Avoidance Method". In order to improve the credibility of the results, the experiment should be repeated five times, each time using an independent sample, and the test results are shown in Table 1. Analysis shows that the graphene quantum dot film prepared by the present invention has excellent antibacterial and anti-mite effects. The modified graphene quantum dots prepared by the present invention have a stronger electronegativity of Cl and a greater valence state of Ce. Co-doping of the two can greatly improve the antibacterial effect and mite removal ability of graphene.

[0038]

[0039] Example 2

[0040] S1. Weigh 3 g sodium citrate, 10 g urea, 2 g cyanuric chloride and 5 g cerium nitrate, then dissolve them in a beaker containing 50 mL N,N-dimethylformamide (DMF), place on a magnetic stirrer, stir for 20 min, transfer to a 100 mL autoclave, and react at 190 °C for 10 h. After the reaction is completed, cool to room temperature. Take out the brown-black solution after the reaction, then mix the solution after the reaction with ethanol in a volume ratio of 1:2, and ultrasonicate for 5 min at 8000 r min. -1The product was centrifuged on a high-speed refrigerated centrifuge for 11 min, and the obtained product was dissolved in ethanol again, ultrasonicated for 5 min, and centrifuged for 15 min. After repeated washing twice, the obtained black solid product was dissolved in water, ultrasonicated for 7 min to make it quickly dispersed, and placed in a dialysis bag with a molecular weight cutoff of 2000D, and dialyzed in a 1L beaker. Ultrapure water was replaced every 4 hours on the first day, and then every 8 hours. After dialysis for 48 hours, the solution was poured into a 50 mL round-bottom flask and concentrated to 10-30 mL using a rotary evaporator. The rotary evaporation temperature was controlled at 55°C, and then placed in a 50 mL centrifuge tube. The freeze-dried material was freeze-dried using a freeze dryer to obtain a black solid, which was graphene co-doped with Ce and Cl. In this step, Cl has a strong electronegativity and Ce has a large valence state. The co-doping of the two can greatly improve the mechanical properties and antibacterial effects of graphene, and the introduction of Ce and Cl is conducive to dispersing graphene sheets through electrostatic repulsion and better controlling the number of layers of the material.

[0041] S2. Take 50 mL of 0.3M sodium hypophosphite solution and place it in a 100 mL microwave reactor. Add 9 g of Ce and Cl co-doped graphene prepared in step S1, stir evenly, and ultrasonicate for 40 min. Place the reactor in a microwave reactor. Set the temperature to 150°C, the microwave power to 300 W, and the microwave time to 20 min. After cooling to room temperature, heat the liquid at 9000 r min. -1 The mixture was centrifuged in a high-speed centrifuge for 10 min and dried to obtain graphene quantum dots co-doped with Ce and Cl containing P. Ultrasonic treatment in this step is beneficial to nano-fiberization of graphene. Phosphating under microwave action is beneficial to the segmentation of graphene to prepare graphene quantum dots, avoiding the reaggregation of quantum dots. In addition, there is a synergistic effect between P, Ce and Cl, which ensures that graphene quantum is well dispersed, exhibits good antibacterial properties and ensures excellent biocompatibility.

[0042] S3, weigh 15 g of the modified graphene quantum dots prepared in step S2, 19 g of the high molecular weight polymer polysulfone and 0.7 g of polyimide, dissolve them in a beaker containing 6 mL of polyethylene glycol and 68 mL of dimethylacetamide, and then put them in a magnetic stirrer and stir for 42 min to obtain a casting solution; the stirred casting solution is allowed to stand for degassing for 40 h until the solution is uniform and free of bubbles. When scraping the film, first place the casting solution on a polyester non-woven fabric that has been uniformly soaked with dimethylacetamide on a glass plate, and then use an automatic scraping machine to evenly apply a coating with a thickness of 0.2 mm. After evaporating in the air for 18 s, immediately place the polyester non-woven fabric coated with the casting solution in deionized water at 25°C for phase inversion, then take out the film and repeatedly wash it with deionized water, and store it in deionized water for standby use. When scraping the film, the relative humidity of the environment is controlled at 40%, and the ambient temperature is controlled at 25°C, and a film containing modified graphene quantum dots can be obtained.

[0043] Comparative Example 4: In step S1, except that 2 g of cyanuric chloride is not added, the remaining steps are the same as those of Example 2.

[0044] Comparative Example 5: In step S1, except that 2 g of cyanuric chloride is replaced by 2 g of cyanuric chloride, the remaining steps are the same as those in Example 1.

[0045] Comparative Example 6: In step S1, except that 5 g of cerium nitrate and 2 g of cyanuric chloride are not added, the remaining steps are the same as those in Example 1.

[0046] Figure 2 This is a transmission electron microscope image of the modified graphene quantum dots prepared in Example 2 of the present invention. It can be seen from the figure that the graphene quantum dots prepared in the present invention are composed of small two-dimensional nanomaterial particles with a size between 1 and 10 nm. Phosphating under the action of microwaves, the introduction of P quickly splits the graphene to prepare graphene quantum dots, avoiding the reagglomeration of the quantum dots, but the overall structure still maintains a two-dimensional layered structure. The graphene samples prepared in Example 2 of the present invention and Comparative Example 6 were deposited on single crystal silicon and subjected to atomic force microscopy (AFM) scanning tests. Figure 3 This is an AFM scan of the modified graphene prepared in Example 2 of the present invention. Figure 4 This is an AFM scan of the graphene prepared in Comparative Example 6 of the present invention. It can be seen from the figure that the thickness of the modified graphene prepared in Example 2 is about 1.3 nm, while the thickness of the graphene prepared in Comparative Example 6 is about 0.7 nm. It can be concluded that the present invention adjusts the physical and chemical properties of the material by introducing heteroatoms through doping modification, adjusting the distance between graphene layers, and controlling its stacking mode. The two-dimensional sheet structure of modified graphene provides broad application prospects in the fields of energy storage, catalysis, sensing, biomedicine, and electronic devices.

[0047] Example 3

[0048] S1. Weigh 2.5 g sodium citrate, 8 g urea, 1.5 g cyanuric chloride and 4 g cerium nitrate, then dissolve them in a beaker containing 44 mL N,N-dimethylformamide (DMF), place on a magnetic stirrer, stir for 18 min, transfer to a 100 mL autoclave, and react at 170 °C for 9 h. After the reaction is completed, cool to room temperature. Take out the brown-black solution after the reaction, then mix the solution after the reaction with ethanol in a volume ratio of 1:2, ultrasonicate for 4 min, and heat at 8000 r min. -1The product was centrifuged on a high-speed refrigerated centrifuge for 9 min, and the obtained product was dissolved in ethanol again, ultrasonicated for 4 min, and centrifuged for 12 min. After repeated washing twice, the obtained black solid product was dissolved in water, ultrasonicated for 6 min to make it quickly dispersed, and placed in a dialysis bag with a molecular weight cutoff of 1000D, and dialyzed in a 1L beaker. Ultrapure water was replaced every 4 hours on the first day, and then every 8 hours. After dialysis for 48 hours, the solution was poured into a 50 mL round-bottom flask and concentrated to 20 mL using a rotary evaporator. The rotary evaporation temperature was controlled at 54 ° C, and then loaded into a 50 mL centrifuge tube. The freeze-dried material was freeze-dried using a freeze dryer to obtain a black solid, which was graphene co-doped with Ce and Cl. In this step, Cl has a strong electronegativity and Ce has a large valence state. The co-doping of the two can greatly improve the mechanical properties and antibacterial effects of graphene, and the introduction of Ce and Cl is conducive to dispersing graphene sheets through electrostatic repulsion and better controlling the number of layers of the material.

[0049] S2. Take 42 mL of 0.2 M sodium hypophosphite solution and place it in a 100 mL microwave reactor. Add 7 g of Ce and Cl co-doped graphene prepared in step S1, stir evenly, and ultrasonicate for 40 min. Place the reactor in a microwave reactor. Set the temperature to 140°C, the microwave power to 400 W, and the microwave time to 26 min. After cooling to room temperature, heat the liquid at 9000 r min. -1 The mixture was centrifuged in a high-speed centrifuge for 10 min and dried to obtain graphene quantum dots co-doped with Ce and Cl containing P. Ultrasonic treatment in this step is beneficial to nano-fiberization of graphene. Phosphating under microwave action is beneficial to the segmentation of graphene to prepare graphene quantum dots, avoiding the reaggregation of quantum dots. In addition, there is a synergistic effect between P, Ce and Cl, which ensures that graphene quantum is well dispersed, exhibits good antibacterial properties and ensures excellent biocompatibility.

[0050] S3, weigh 9 g of the modified graphene quantum dots prepared in step S2, dissolve in 36 mL of N,N-dimethylformamide and 28 mL of anhydrous ethanol, then add 4 mL of 30% H2O2, stir for 9 min, then add 7 g of polyvinyl pyrrolidone and 13 mL of 2-methoxyethanol, stir for 17 h. The reaction is quite violent, so safety precautions should be taken. Then put the mixed solution into a syringe for the next step. Apply a voltage of 14 kV between the syringe and the aluminum foil at a distance of 16 cm. -1 The mixed solution is ejected at a rate of , and nanofibers containing modified graphene are formed by electrospinning.

[0051] Comparative Example 7: In step S2, except that pure water is used to replace the 0.2 M sodium hypophosphite solution, the remaining steps are the same as those in Example 3.

[0052] Figure 5 This is a transmission electron microscope high-resolution image of the modified graphene quantum dots prepared in Example 3 of the present invention; Figure 6 This is a high-resolution transmission electron microscope image of the modified graphene quantum dots prepared in comparative example 7 of the present invention. As can be seen from the comparison in the figure, the modified graphene quantum dots prepared in Example 3 of the present invention have good dispersibility. This shows that the phosphating under the action of microwaves in the present invention is conducive to segmenting graphene to prepare graphene quantum dots, and avoids the reaggregation of quantum dots. It has good conductivity, high stability in electrochemical environment, and good biocompatibility, which broadens the application range of graphene quantum dots.

[0053] Example 4

[0054] S1. Weigh 2.6 g sodium citrate, 9 g urea, 1.8 g cyanuric chloride and 4.2 g cerium nitrate, then dissolve them in a beaker containing 37 mL N,N-dimethylformamide (DMF), place on a magnetic stirrer, stir for 19 min, transfer to a 100 mL autoclave, and react at 170 °C for 8.6 h. After the reaction is completed, cool to room temperature. Take out the brown-black solution after the reaction, then mix the solution after the reaction with ethanol in a volume ratio of 1:2, and ultrasonicate for 4 min at 8000 r min. -1 The product was centrifuged on a high-speed refrigerated centrifuge for 9 min, and the obtained product was dissolved in ethanol again, ultrasonicated for 3 min, and centrifuged for 13 min. After repeated washing twice, the obtained black solid product was dissolved in water, ultrasonicated for 5-7 min to make it quickly dispersed, and placed in a dialysis bag with a molecular weight cutoff of 2000D, and dialyzed in a 1L beaker. Ultrapure water was replaced every 4 hours on the first day, and then every 8 hours. After dialysis for 48 hours, the solution was poured into a 50 mL round-bottom flask and concentrated to 19 mL using a rotary evaporator. The rotary evaporation temperature was controlled at 50 ° C, and then loaded into a 50 mL centrifuge tube. The freeze-dried material was freeze-dried using a freeze dryer to obtain a black solid, which was graphene co-doped with Ce and Cl. In this step, Cl has a strong electronegativity and Ce has a large valence state. The co-doping of the two can greatly improve the mechanical properties and antibacterial effects of graphene, and the introduction of Ce and Cl is conducive to dispersing graphene sheets through electrostatic repulsion and better controlling the number of layers of the material.

[0055] S2, take 45 mL of 0.25 M sodium hypophosphite solution and place it in a 100 mL microwave reactor, add 7 g of Ce and Cl co-doped graphene prepared in step S1, stir evenly, and ultrasonicate for 40 min. Place the reactor in a microwave reactor. Set the temperature to 140°C, the microwave power to 500 W, and the microwave time to 26 min. After cooling to room temperature, heat the liquid at 9000 r min.-1 The mixture was centrifuged in a high-speed centrifuge for 10 min and dried to obtain graphene quantum dots co-doped with Ce and Cl containing P. Ultrasonic treatment in this step is beneficial to nano-fiberization of graphene. Phosphating under microwave action is beneficial to the segmentation of graphene to prepare graphene quantum dots, avoiding the reaggregation of quantum dots. In addition, there is a synergistic effect between P, Ce and Cl, which ensures that graphene quantum is well dispersed, exhibits good antibacterial properties and ensures excellent biocompatibility.

[0056] S3, weigh 9 g of the modified graphene quantum dots prepared in step S2, dissolve in 37 mL of N,N-dimethylformamide and 29 mL of anhydrous ethanol, then add 4 mL of 30% H2O2, stir for 9 min, then add 7 g of polyvinyl pyrrolidone and 13 mL of 2-methoxyethanol, stir for 18 h. The reaction is quite violent, so safety precautions should be taken. Then put the mixed solution into a syringe for the next step. Apply a voltage of 17 kV between the syringe and the aluminum foil at a distance of 16 cm. -1 The mixed solution is ejected at a rate of , and nanofibers containing modified graphene are formed by electrospinning.

[0057] Comparative Example 8: In step S1, cerium nitrate was not added, and in step S2, pure water was used instead of the sodium hypophosphite solution. The remaining steps were the same as those in Example 4.

[0058] Figure 7 This is a transmission electron microscope image of the nanofibers prepared in Example 4 of the present invention. Figure 8 The transmission electron microscope image of the nanofiber prepared in comparative example 8 of the present invention is shown in FIG. From the analysis of the image, it can be seen that the nanofiber containing modified graphene prepared in the present invention is not easy to break, while the nanofiber prepared in comparative example 8 breaks. This shows that there is a certain synergistic effect between Ce doping and P addition, which promotes the prepared nanofiber to be unbroken, thereby ensuring its good mechanical properties.

[0059] The above-mentioned embodiments only express the specific implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present invention. It should be pointed out that, for those skilled in the art, without departing from the concept of the present invention, any other changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A modified graphene, characterized in that: The specific preparation method is as follows: weigh 2-3 g of sodium citrate, 5-10 g of urea, 1-2 g of cyanuric chloride and 3-5 g of cerium nitrate, then dissolve them in a beaker containing 30-50 mL of N,N-dimethylformamide, then place them on a magnetic stirrer, stir for 15-20 min, transfer them to a 100 mL high-pressure reactor, and react at a constant temperature of 150-190 ° C for 8-10 h; after the reaction is completed, cool to room temperature; take out the brown-black solution after the reaction, then mix the solution after the reaction with ethanol in a volume ratio of 1:2, and ultrasonicate for 3-5 min and then rotate at 8000 r min -1 The product was centrifuged in a high-speed refrigerated centrifuge for 8-11 min, and the obtained product was dissolved in ethanol again, ultrasonicated for 2-5 min, and centrifuged for 10-15 min, and repeated twice. After washing, the obtained black solid product was dissolved in water, ultrasonicated for 5-7 min to disperse it quickly, and loaded into a dialysis bag with a molecular weight cutoff of 1000D-2000D, and dialyzed in a 1L beaker. Ultrapure water was replaced every 4 hours on the first day, and then every 8 hours. After dialysis for 48 hours, the solution was poured into a 50 mL round-bottom flask and concentrated to 10-30 mL using a rotary evaporator. The rotary evaporation temperature was controlled at 50-55°C, and then loaded into a 50 mL centrifuge tube. The material was freeze-dried using a freeze dryer to obtain a black solid, which is Ce and Cl co-doped graphene.

2. A modified graphene according to claim 1, characterized in that: Weigh 2 g of sodium citrate, 5 g of urea, 1 g of cyanuric chloride and 3 g of cerium nitrate, then dissolve them in a beaker containing 30 mL of N,N-dimethylformamide, place them on a magnetic stirrer, stir for 15 min, transfer them to a 100 mL high-pressure reactor, and react at a constant temperature of 150 °C for 8 h; after the reaction is completed, cool to room temperature; take out the brown-black solution after the reaction, then mix the solution after the reaction with ethanol in a volume ratio of 1:2, and ultrasonicate for 3 min at 8000 r min -1 The product was centrifuged in a high-speed refrigerated centrifuge for 8 min, and the obtained product was dissolved in ethanol again, ultrasonicated for 2 min, and centrifuged for 10 min. After repeated washing twice, the obtained black solid product was dissolved in water, ultrasonicated for 5 min to make it quickly dispersed, and loaded into a dialysis bag with a molecular weight cutoff of 1000D, and dialyzed in a 1L beaker. Ultrapure water was replaced every 4 hours on the first day, and then every 8 hours. After dialysis for 48 hours, the solution was poured into a 50 mL round-bottom flask and concentrated to 10 mL using a rotary evaporator. The rotary evaporation temperature was controlled at 50 ℃, and then loaded into a 50 mL centrifuge tube. The material was freeze-dried using a freeze dryer to obtain a black solid, which is Ce and Cl co-doped graphene.

3. A modified graphene according to claim 1, characterized in that: Weigh 3 g of sodium citrate, 10 g of urea, 2 g of cyanuric chloride and 5 g of cerium nitrate, then dissolve them in a beaker containing 50 mL of N,N-dimethylformamide, place them on a magnetic stirrer, stir for 20 min, transfer them to a 100 mL high-pressure reactor, and react at 190 °C for 8-10 h; after the reaction is completed, cool to room temperature; take out the brown-black solution after the reaction, then mix the solution after the reaction with ethanol in a volume ratio of 1:2, and ultrasonicate for 5 min at 8000 r min -1 The product was centrifuged in a high-speed refrigerated centrifuge for 11 min, and the obtained product was dissolved in ethanol again, ultrasonicated for 5 min, and centrifuged for 15 min. After repeated washing twice, the obtained black solid product was dissolved in water, ultrasonicated for 7 min to make it quickly dispersed, and loaded into a dialysis bag with a molecular weight cutoff of 1000D-2000D, and dialyzed in a 1L beaker. Ultrapure water was replaced every 4 hours on the first day, and then every 8 hours. After dialysis for 48 hours, the solution was poured into a 50 mL round-bottom flask and concentrated to 30 mL using a rotary evaporator. The rotary evaporation temperature was controlled at 55°C, and then loaded into a 50 mL centrifuge tube. The material was freeze-dried using a freeze dryer to obtain a black solid, which is Ce and Cl co-doped graphene.

4. A modified graphene quantum dot, characterized in that: The specific preparation method is as follows: S1, weigh 2-3 g of sodium citrate, 5-10 g of urea, 1-2 g of cyanuric chloride and 3-5 g of cerium nitrate, and then dissolve them in a beaker containing 30-50 mL of N,N-dimethylformamide, then place them on a magnetic stirrer, stir for 15-20 min, transfer them to a 100 mL high-pressure reactor, and react at a constant temperature of 150-190 ° C for 8-10 h; after the reaction is completed, cool to room temperature; take out the brown-black solution after the reaction, and then mix the solution after the reaction with ethanol in a volume ratio of 1:2, and ultrasonicate for 3-5 min and then rotate at 8000 r min -1 The product was centrifuged in a high-speed refrigerated centrifuge for 8-11 min, and the obtained product was dissolved in ethanol again, ultrasonicated for 2-5 min, and centrifuged for 10-15 min. After repeated washing twice, the obtained black solid product was dissolved in water, ultrasonicated for 5-7 min to make it quickly dispersed, and loaded into a dialysis bag with a molecular weight cutoff of 1000D-2000D, and dialyzed in a 1L beaker. Ultrapure water was replaced every 4 hours on the first day, and then every 8 hours. After dialysis for 48 hours, the solution was poured into a 50 mL round-bottom flask and concentrated to 10-30 mL using a rotary evaporator. The rotary evaporation temperature was controlled at 50-55°C, and then loaded into a 50 mL centrifuge tube. The material was freeze-dried using a freeze dryer to obtain a black solid, which is Ce and Cl co-doped graphene; S2, take 35-50 mL of 0.15-0.3M sodium hypophosphite solution and place it in a 100 mL microwave reactor, add 5-9 g of Ce and Cl co-doped graphene prepared in step S1, stir evenly, and ultrasonically treat for 40 min; place the reactor in a microwave reactor; set the temperature to 130-150°C, the microwave power to 300-600W, and the microwave time to 20-30 min; after cooling to room temperature, heat the liquid at 9000 r min -1 The resultant was centrifuged in a high-speed centrifuge for 10 min and dried to obtain P-containing Ce and Cl co-doped graphene quantum dots.

5. A modified graphene quantum dot according to claim 4, characterized in that: 35 mL of 0.15 M sodium hypophosphite solution in step S2 was weighed and placed in a 100 mL microwave reactor, 5 g of Ce and Cl co-doped graphene prepared in step S1 was added, stirred evenly, and ultrasonicated for 40 min; the reactor was placed in a microwave reactor; the temperature was set to 130 °C, the microwave power was 300 W, and the microwave time was 20 min; after cooling to room temperature, the liquid was heated at 9000 r min -1 After centrifugation in a high-speed centrifuge for 10 min and drying, P-containing Ce and Cl co-doped graphene quantum dots can be obtained.

6. A modified graphene quantum dot according to claim 4, characterized in that: 50 mL of 0.3 M sodium hypophosphite solution in step S2 was weighed and placed in a 100 mL microwave reactor, 9 g of Ce and Cl co-doped graphene prepared in step S1 was added, stirred evenly, and ultrasonicated for 40 min; the reactor was placed in a microwave reactor; the temperature was set to 150°C, the microwave power was 600 W, and the microwave time was 30 min; after cooling to room temperature, the liquid was heated at 9000 r min -1 The resultant was centrifuged in a high-speed centrifuge for 10 min and dried to obtain P-containing Ce and Cl co-doped graphene quantum dots.

7. A film containing modified graphene quantum dots, characterized in that: The specific preparation method is as follows: S1, weigh 2-3 g of sodium citrate, 5-10 g of urea, 1-2 g of cyanuric chloride and 3-5 g of cerium nitrate, then dissolve them in a beaker containing 30-50 mL of N,N-dimethylformamide, then place them on a magnetic stirrer, stir for 15-20 min, transfer them to a 100 mL high-pressure reactor, and react at a constant temperature of 150-190 ° C for 8-10 h; after the reaction is completed, cool to room temperature; take out the brown-black solution after the reaction, then mix the solution after the reaction with ethanol in a volume ratio of 1:2, and ultrasonicate for 3-5 min and then rotate at 8000 rmin -1 The product was centrifuged in a high-speed refrigerated centrifuge for 8-11 min, and the obtained product was dissolved in ethanol again, ultrasonicated for 2-5 min, and centrifuged for 10-15 min. After repeated washing twice, the obtained black solid product was dissolved in water, ultrasonicated for 5-7 min to disperse it quickly, and placed in a dialysis bag with a molecular weight cutoff of 1000D-2000D, and dialyzed in a 1L beaker. Ultrapure water was replaced every 4 hours on the first day, and then every 8 hours. After dialysis for 48 hours, the solution was poured into a 50 mL round-bottom flask and concentrated to 10-30 mL using a rotary evaporator. The rotary evaporation temperature was controlled at 50-55°C, and then placed in a 50 mL centrifuge tube. The material was freeze-dried using a freeze dryer to obtain a black solid, which is Ce and Cl co-doped graphene; S2, take 35-50 mL of 0.15-0.3M sodium hypophosphite solution and place it in a 100 mL microwave reactor, add 5-9 g of Ce and Cl co-doped graphene prepared in step S1, stir evenly, and ultrasonically treat for 40 min. Place the reactor in a microwave reactor. Set the temperature to 130-150℃, the microwave power to 300-600W, and the microwave time to 20-30 min; after cooling to room temperature, heat the liquid at 9000 r min. -1 The mixture was centrifuged in a high-speed centrifuge for 10 min and dried to obtain P-containing Ce and Cl co-doped graphene quantum dots. S3, weighing 9-18 g of the modified graphene quantum dots prepared in step S2, 13-27 g of the high molecular weight polymer polysulfone and 0.5-0.8 g of polyimide, dissolving them in a beaker containing 5-8 mL of polyethylene glycol and 60-75 mL of dimethylacetamide, and then placing them in a magnetic stirrer and stirring for 30-45 min to obtain a casting solution; standing the stirred casting solution for degassing for 36-48 h until the solution is uniform and free of bubbles; when scraping the film, first place the casting solution on a polyester non-woven fabric that has been uniformly soaked with dimethylacetamide and attached to a glass plate, and then use an automatic scraping machine to evenly apply a coating with a thickness of 0.2-0.5 mm, and evaporate it in the air for 15-30 s, the polyester non-woven fabric coated with the casting liquid is immediately placed in deionized water at 25°C for phase inversion, and then the membrane is taken out and repeatedly washed with deionized water and stored in deionized water for later use; when scraping the membrane, the relative humidity of the environment is controlled at 40%-50%, and the ambient temperature is controlled at 25°C, and a thin film containing modified graphene quantum dots can be obtained.

8. A film containing modified graphene quantum dots according to claim 7, characterized in that: In the step S3, 9 g of the modified graphene quantum dots prepared in step S2, 13 g of the high molecular weight polymer polysulfone and 0.5 g of polyimide are weighed and dissolved in a beaker containing 5 mL of polyethylene glycol and 60 mL of dimethylacetamide, and then placed in a magnetic stirrer and stirred for 30 min to obtain a casting solution; the stirred casting solution is allowed to stand for degassing for 36 h until the solution is uniform and free of bubbles; when scraping the film, the casting solution is first placed on a polyester non-woven fabric that has been uniformly soaked with dimethylacetamide and attached to a glass plate, and then an automatic film scraping machine is used to uniformly apply a coating with a thickness of 0.2 mm. After evaporating in the air for 15 s, the polyester non-woven fabric coated with the casting solution is immediately placed in deionized water at 25°C for a phase inversion process, and then the film is taken out and repeatedly washed with deionized water, and stored in deionized water for standby use; when scraping the film, the relative humidity of the environment is controlled at 40% and the ambient temperature is controlled at 25°C, so that a thin film containing modified graphene quantum dots can be obtained.

9. A film containing modified graphene quantum dots according to claim 7, characterized in that: In the step S3, 18 g of the modified graphene quantum dots, 27 g of the high molecular weight polymer polysulfone and 0.8 g of polyimide prepared in step S2 are weighed and dissolved in a beaker containing 8 mL of polyethylene glycol and 75 mL of dimethylacetamide, and then placed in a magnetic stirrer and stirred for 45 min to obtain a casting solution; the stirred casting solution is allowed to stand for degassing for 48 h until the solution is uniform and free of bubbles; when scraping the film, the casting solution is first placed on a polyester non-woven fabric that has been uniformly soaked with dimethylacetamide and attached to a glass plate, and then an automatic film scraping machine is used to uniformly apply a coating with a thickness of 0.5 mm. After evaporating in the air for 30 s, the polyester non-woven fabric coated with the casting solution is immediately placed in deionized water at 25°C for a phase inversion process, and then the film is taken out and repeatedly washed with deionized water, and stored in deionized water for standby use; when scraping the film, the relative humidity of the environment is controlled at 50% and the ambient temperature is controlled at 25°C, so that a thin film containing modified graphene quantum dots can be obtained.

10. A nanofiber containing modified graphene, characterized in that: The specific preparation method is as follows: S1, weigh 2-3 g of sodium citrate, 5-10 g of urea, 1-2 g of cyanuric chloride and 3-5 g of cerium nitrate, then dissolve them in a beaker containing 30-50 mL of N,N-dimethylformamide, then place them on a magnetic stirrer, stir for 15-20 min, transfer them to a 100 mL high-pressure reactor, and react at a constant temperature of 150-190 ° C for 8-10 h; after the reaction is completed, cool to room temperature; take out the brown-black solution after the reaction, then mix the solution after the reaction with ethanol in a volume ratio of 1:2, and ultrasonicate for 3-5 min and then rotate at 8000 rmin -1 The product was centrifuged in a high-speed refrigerated centrifuge for 8-11 min, and the obtained product was dissolved in ethanol again, ultrasonicated for 2-5 min, and centrifuged for 10-15 min. After repeated washing twice, the obtained black solid product was dissolved in water, ultrasonicated for 5-7 min to disperse it quickly, and placed in a dialysis bag with a molecular weight cutoff of 1000D-2000D, and dialyzed in a 1L beaker. Ultrapure water was replaced every 4 hours on the first day, and then every 8 hours. After dialysis for 48 hours, the solution was poured into a 50 mL round-bottom flask and concentrated to 10-30 mL using a rotary evaporator. The rotary evaporation temperature was controlled at 50-55°C, and then placed in a 50 mL centrifuge tube. The material was freeze-dried using a freeze dryer to obtain a black solid, which is Ce and Cl co-doped graphene; S2, take 35-50 mL of 0.15-0.3M sodium hypophosphite solution and place it in a 100 mL microwave reactor, add 5-9 g of Ce and Cl co-doped graphene prepared in step S1, stir evenly, and ultrasonically treat for 40 min; place the reactor in a microwave reactor; set the temperature to 130-150°C, the microwave power to 300-600W, and the microwave time to 20-30 min; after cooling to room temperature, heat the liquid at 9000 r min -1 The mixture was centrifuged in a high-speed centrifuge for 10 min and dried to obtain P-containing Ce and Cl co-doped graphene quantum dots. S3, weigh 8-11 g of the modified graphene quantum dots prepared in step S2, dissolve in 30-40 mL of N,N-dimethylformamide and 20-32 mL of anhydrous ethanol, then add 3-5 mL of 30% H2O2, stir for 8-10 min, then add 5-8 g of polyvinyl pyrrolidone and 10-15 mL of 2-methoxyethanol, stir for 12-20 h; then put the mixed solution into a syringe for the next step; apply a voltage of 13-18 kV between the syringe and the aluminum foil at a distance of 15-20 cm; and at a rate of 0.4-0.6 mL / h -1 The mixed solution is sprayed at a rate of , and nanofibers containing modified graphene are formed by electrostatic spinning; the graphene nanofibers prepared by electrostatic spinning in this step have a content of 0.1-0.5%.